If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + -21 = 46 Reorder the terms: -21 + 13x = 46 Solving -21 + 13x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 13x = 46 + 21 Combine like terms: -21 + 21 = 0 0 + 13x = 46 + 21 13x = 46 + 21 Combine like terms: 46 + 21 = 67 13x = 67 Divide each side by '13'. x = 5.153846154 Simplifying x = 5.153846154
| x-7=24 | | 8x^3+40x^2-288x= | | 5(x+2)-2x(3x-1)=13 | | 0=x^2+5x-15 | | 2x+5=x+13 | | 300-90= | | 25*12= | | 4x^2-16x+24=0 | | 2(4a+3)=16 | | x-4y=-13 | | 6x+19=1056 | | -2(x-3)=10 | | x-9=3x+11 | | 6x-8=8x+2 | | C^2-4c=-3 | | -q^2+5q-4=0 | | r^2+4r+6=0 | | x+78+x+a+87=199 | | b^2-5b-6=0 | | K^2-7k+12=0 | | 3y-2x=15 | | 48+7m=174 | | 25x-96=104 | | 2x^2-20x+82=0 | | 7+3(x+2)=4(x-1) | | 2x-(3-(4-3x))+6= | | (W+6)(w-15)=0 | | (2c-4)= | | x+23-45=4x+34 | | 93567489e= | | 1e= | | 3(4z-5)=6-(7-2z) |